The biomechanical evaluation of metacarpal fractures fixation methods during finger movements: a finite element study - Liu, Mingrui; Luo, Lincong; Lin, Tao; Lv, Xiaoyu; Vashisth, Manoj Kumar; Li, Jiaying; Shen, Jianlin; Xu, Lin; Huang, Wenhua (Frontiers in Bioengineering and Biotechnology, 2024)
Abstract Objective: This study used finite element analysis to simulate four commonly used fixation methods for metacarpal shaft oblique fractures during finger motion and evaluate their biomechanical performance. The aim was to provide evidence for clinically selecting the optimal fixation method, guiding early rehabilitation treatment, and reducing the risk of complications. Methods: Finite element analysis simulated dynamic proximal phalanx motion (60° flexion, 20° extension, 20° adduction, and 20° abduction). We analysed stress, displacement, and distributions for dorsal plates, intramedullary nails, Kirschner wire, and screw fixation methods. Results: At 60° of finger flexion and 20° of abduction, plate fixation demonstrated greater stability and minimal displacement, with a peak displacement of 0.19mm; however, it showed higher stress levels in all motion states, increasing the risk of failure. The stability of the intramedullary nail was similar to that of the dorsal plate, with a maximum displacement difference of 0.04mm, and it performed better than the dorsal plate during adduction of 20°. Kirschner wire showed the highest stress levels of 81.6 Mpa during finger flexion of 60°, indicating a greater risk of failure and unstable displacement. Screws had lower stress levels in all finger motion states, reducing the risk of failure, but had poorer stability. Stress and displacement distributions showed that the dorsal plate, intramedullary nail, and Kirschner wire mainly bore stress on the implants, concentrating near the fracture line and the proximal metacarpal. In contrast, the screws partially bore stress in the screw group. The anterior end of the metacarpal mainly hosted the maximum displacement. Conclusion: This study demonstrates that under simulated finger motion states, the dorsal plate fixation method provides the best stability in most cases, especially during finger flexion and abduction. However, high stress levels also indicate a higher risk of failure. The intramedullary nail is similar to the dorsal plate in stability and performs better in certain motion states. Kirschner wire exhibits the highest risk of failure during flexion. Although screws have poorer stability in some motion states, they offer a lower risk of failure. These findings provide important reference and surgical selection strategies for treating metacarpal fractures.